PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, LEVERAGE, UKURAN PERUSAHAAN DAN SALES GROWTH TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2016) - Yunita Indra Dewi, 14.05.52.0095; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the effect of agencies, committee audit, leverage, company size and sales growth on tax avoidance in companies listed on the Stock Exchange in 2014-2016. The population is all manufacturing companies listed on the IDX for the period 2014-2016. The sampling technique in this study was conducted using purposive sampling method. The data obtained were analyzed using multiple linear regression analysis. The experimental results can be concluded that institutional ownership does not affect tax avoidance. The Audit Committee is inadequate against tax evasion. Utilizing a negative attitude towards tax avoidance. Company Size Produces Negatives Against Tax Avoidance. Sales growth does not result in tax evasion Keywords: institutional ownership, committee audit, leverage, company size, sales growth and tax avoidance